Bioavailability of citrus flavanones and its effect on cardiometabolic parameters in humans - Fraga, Layanne Nascimento (2023)
Hesperidin and narirutin are the main flavonoids present in orange juice (OJ). Chronic consumption of OJ has been associated with a reduction in the occurrence of cardiometabolic diseases. However, considerable inter-individual variability is observed in the biological response associated with OJ consumption, in part due to the inter-individual variability in the bioavailability of these bioactive compounds. The objectives of this study were to identify the factors that influence the bioavailability of flavanones and evaluate the effects of chronic consumption of OJ on cardiometabolic parameters. The study volunteers comprised 85 eutrophic (19-24.9 kg/m2) or overweight (25-29.9 kg/m2) men and women between the ages of 18 and 40. For 60 days, the volunteers consumed 500 mL of OJ daily. To assess the effects of this intervention, anthropometric measurements, blood pressure measurements, and fasting blood, urine, and feces samples were collected on the first day of the test and after 30 and 60 days of intervention. After the first single-dose OJ intake, a 24-hour urine sample was also collected; in these samples, flavanone metabolites were identified and quantified by LC-qTOFMS/MS. After 60 days of OJ ingestion, substantial heterogeneity was observed in the responses of the biochemical, anthropometric, and blood pressure data: some individuals responded to the intervention, while others did not. However, significant reductions in fat percentage and blood pressure were observed. Several phase II flavanone metabolites (sulfated and glucuronidated) and phenolic acids derived from their metabolization by intestinal microbiota were identified in the urine. There was notable metabolite excretion variability that was not influenced by gender or BMI. Thus, the volunteers were classified as high, medium, or low excretors based on the excreted amount of phase II conjugated metabolites and phenolic acids. Variations in flavanone metabolite excretion were associated with the presence of single nucleotide polymorphisms (SNPs) in genes for sulfotransferase (SULT1A1, SULT1C4), a phase II metabolic enzyme, and the ABCC2 transporter. Using this approach, responsiveness to OJ intake was primarily attributed to phase II flavanone conjugates, although the importance of phenolic acids cannot be ruled out. SNPs in the APOE, APOA1, and LPL genes were related to heterogeneity in lipid profiles and blood pressure after chronic OJ ingestion. These results demonstrate that responsiveness to orange juice intake depends on an individual\'s ability to metabolize citrus flavanones and the presence of polymorphisms in certain metabolic genes. These findings may inform new approaches in personalized nutrition that promote the consumption of foods rich in flavanones, given their health benefits.